Detection of Trichomonas vaginalis Using the Polymerase Chain Reaction in Pregnant and Non-Pregnant Women - J. Jeremias; D. Draper; M. Ziegert; W. Jones; S. Inglis; J. A. McGregor; S. S. Witkin (Hindawi Limited, 1994)
Objective:Trichomonas vaginalis vaginal infections are often both asymptomatic and difficult to detect by current methods. We evaluated the ability of a newly developed polymerase chain reaction (PCR) assay to identify T. vaginalis in vaginal samples from pregnant and non-pregnant women.